A girl's guide to moving on [large type] : a novel - Macomber, Debbie (Macomber, Debbie. New beginnings series., 2016)
When Nichole discovers that her husband, Jake, has been unfaithful, the illusion of her perfect life is indelibly shattered. While juggling her young son, a new job, and volunteer work, Nichole meets Rocco, who is the opposite of Jake in nearly every way. Though blunt-spoken and rough around the edges, Rocco proves to be a dedicated father and thoughtful friend. But just as their relationship begins to blossom, Jake wagers everything on winning Nichole back<U+2014>including their son Owen<U+2019>s happiness. Somehow, Nichole must find the courage to defy her fears and follow her heart, with far-reaching consequences for them all. Leanne has quietly ignored her husband<U+2019>s cheating for decades, but is jolted into action by the echo of Nichole<U+2019>s all-too-familiar crisis. While volunteering as a teacher of English as a second language, Leanne meets Nikolai, a charming, talented baker from Ukraine. Resolved to avoid the heartache and complications of romantic entanglements, Leanne nonetheless finds it difficult to resist Nikolai<U+2019>s effusive overtures<U+2014>until an unexpected tragedy tests the very fabric of her commitments.